Alentejo Rough Guides Snapshot Portugal (includes Évora, Estremoz, Alter do Chão, Crato Portalegre, Castelo de Vide, Marvão, Elvas, Vila Viçosa, Monsaraz, Moura, Serpa, Beja, Mértola, Alcácer do Sal, Comporta and Santiago do Cacém). (2014) - Rough Guides
No abstract available